The impact of the new coronavirus infection COVID-19 on the microcirculation of the eye - O. I. Markelova; S. Yu. Petrov; T. D. Okhotsimskaya (Российский офтальмологический журнал)
The challenge of the coronavirus pandemic, and the research into the mechanism of development of the symptom complex that appears in patients who had COVID-19 (post-COVID syndrome), is a topical issue of modern medicine. Obviously, as the incidence of COVID increases, the number of patients suffering from the post-COVID syndrome increases, too. According to recent estimates, 10 to 20 % of patients who have experienced an acute symptomatic phase of SARS-CoV-2 suffer from the effects of the disease over 12 weeks from the primary diagnosis. COVID-19 has been shown to have a variety of long-term effects on virtually all body systems, including the eye. The ocular surface can serve as a gateway for the virus to enter the body, so that patients experience nonspecific changes in the conjunctiva, cornea, retina, and eye vessels. Thus, the issues of diagnosis and treatment of the COVID-19 infection itself and, notably, its complications and conditions that have arisen and continue after the disease, are of essential research and clinical interest. SARS-CoV-2 has a negative impact on the state of the vascular wall and contributes to the development of hypercoagulable conditions, which increases the risk of thrombosis and possible complications in the cardiovascular system. The review summarizes the analyses of eye vessels blood flow in patients who have undergone COVID-19.